Experimental validation of more realistic computer models for stent‐graft repair of abdominal aortic aneurysms, including pre‐load assessment. (2nd March 2016) - Roy, David; Lerouge, Sophie; Inaekyan, Karina; Kauffmann, Claude; Mongrain, Rosaire; Soulez, Gilles
Summary: Although the endovascular repair of abdominal aortic aneurysms is a less invasive alternative than classic open surgery, complications such as endoleak and kinking still need to be addressed. Numerical simulation of endovascular repair is becoming a valuable tool in stent‐graft (SG) optimization, patient selection and surgical planning. The experimental and numerical forces required to produce SG deformations were compared in a range of in vivo conditions in the present study. The deformation modes investigated were: bending as well as axial, transversal and radial compressions. In particular, an original method was developed to efficiently account for radial pre‐load because of the pre‐compression of stents to match the graft dimensions during manufacturing. This is important in order to compute the radial force exerted on the vessel after deployment more accurately. Variations of displacement between the experimental and numerical results ranged from 1.39% for simple leg bending to 5.93% for three‐point body bending. Finally, radial pre‐load was modeled by increasing Young's modulus of each stent. On average, it was found that Young's modulus had to be augmented by a factor of 2. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : In validating numerical SGs against mechanical tests, bending and axial, transversal and radial compressions were performed. Variations of displacement between the experimental and numerical results ranged from 1.27% for the simple bending of leg, to 5.93% for the three‐point bending of body. A linear relationship was found between radial force and radial displacement, up to a diameter reduction of 70%. The radial pre‐load was modeled by increasing the Young's modulus of each stent, by a mean factor of 2.